2020
DOI: 10.1021/acs.jchemed.9b00777
|View full text |Cite
|
Sign up to set email alerts
|

Using Image Recognition and Processing Technology to Measure the Gas Volume in a Miniature Water Electrolysis Device Constructed with Simple Materials

Abstract: This paper proposes an experiment in which students build microdevices for conveniently electrolyzing water and use image recognition and processing technology to measure the volume of gas generated during the reaction in a noncontact way. Taking advantage of three ratio relationships between (i) gas volume and the area of bubbles, (ii) the factual size and the size on the picture, and (iii) the area on the picture and the pixel number, the experiment converts the measurement of trace gas volume into measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…After segmenting the matched data features, since the matched data is a kind of video image, it is necessary to convert the spectrum diagram into simple and easy to analyze matching feature data [23], so as to obtain…”
Section: Realization Of Matching Error Recognition Based On Datamentioning
confidence: 99%
“…After segmenting the matched data features, since the matched data is a kind of video image, it is necessary to convert the spectrum diagram into simple and easy to analyze matching feature data [23], so as to obtain…”
Section: Realization Of Matching Error Recognition Based On Datamentioning
confidence: 99%
“…The main contribution of this research is that it demonstrates that the IR‐based learning approach can improve students' learning motivation and learning attitude in scientific inquiry courses. From the literature up to 2021, it was found that researchers mainly attempted to use IR systems in educational settings (Ling et al., 2020; Shadiev et al., 2020). Whilst the CM‐IR learning approach is a new endeavour, the present study shows that incorporating concept mapping into the use of IR systems can improve student achievement, attitude and internal motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, in chemistry education, the purpose of a water electrolysis experiment has been to obtain experimental evidence that supports the fact that water is composed of hydrogen and oxygen elements. Consequently, water electrolysis experiments have focused on identifying reaction products such as hydrogen gas, oxygen gas, hydroxide ions, and hydrogen ions. This was based on the assumption that electrodes, electrolytes, and indicators did not participate in the water electrolysis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The electrolysis of water containing these anions can generate oxygen gas and increase the number of hydrogen ions at the anode. Therefore, electrolytes such as NaOH, ,,, H 2 SO 4 , ,, Na 2 SO 4 , ,, and KNO 3 ,, are commonly used in water electrolysis. It is expected that hydroxide ions are produced at the cathode, and hydrogen ions are produced at the anode in equimolar quantities under ideal conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation